Survival in low light: photosynthesis and growth of a red alga in relation to measured in situ irradiance. Issue 5 (15th July 2013) - Pritchard, Daniel W.; Hurd, Catriona L.; Beardall, John; Hepburn, Christopher D.; Harley, C.
<x xml:space="preserve">Abstract</x> Reduced light availability for benthic primary producers as a result of anthropogenic activities may be an important driver of change in coastal seas. However, our knowledge of the minimum light requirements for benthic macroalgae limits our understanding of how these changes may affect primary productivity and the functioning of coastal ecosystems. This knowledge gap is particularly acute in deeper water, where the impacts of increased light attenuation will be most severe. We examined the minimum light requirements of Anotrichium crinitum, which dominates near the maximum depth limit for macroalgae throughout New Zealand and Southern Australia, and is a functional analog of rhodophyte macroalgae in temperate low‐light (deep‐water) habitats throughout the world. These data show that A. crinitum is a shade‐adapted seaweed with modest light requirements for the initiation of net photosynthesis (1.49–2.25 μmol photons · m−2 · s−1) and growth (0.12–0.19 mol photons · m−2 · d−1). A. crinitum maintains high photosynthetic efficiency and pigment content and a low C:N ratio throughout the year and can maintain biomass under sub‐compensation (critical) light levels for at least 5 d. Nevertheless, in situ photon flux is less than the minimum light requirement for A. crinitum on at least 103 d per annum and is rarely sufficient to saturate growth. These findings reinforce the importance of understanding the physiological response of macroalgae at the extremes of environmental gradients and highlight the need to establish minimum thresholds that modification of the subtidal light environment should not cross.